An Analysis Of Translation Sentences Containing Derivative Adjective In Agatha Christie's Novel The Murder Of Roger Ackroyd Into Pembunuhan Atas Roger Ackroyd Translated By Maria Regina - Ahmad, Fahruddin Ali (2006)
The purpose of this research is to analyse the translation types of sentences containing derivative adjective in Agatha Christie's The Murder of Roger Ackroyd into Pembunuhan atas Roger Ackroyd translated by Maria Regina. The problems of the study are what the translation types of sentences containing derivative adjective in Agatha Christie's The Murder of Roger Ackroyd into Pembunuhan atas Roger Ackroyd translated by Maria Regina are, and how the translation accuracy of derivative adjective in Agatha Christie's The Murder of Roger Ackroyd into Pembunuhan atas Roger Ackroyd translated by Maria Regina is. To describe the translation types of sentences containing derivative adjective in Agatha Christie's The Murder of Roger Ackroyd into Pembunuhan atas Roger Ackroyd translated by Maria Regina, the writer uses a descriptive qualitative research as the type of research. The data used in this research is taken from the novel The Murder of Roger Ackroyd by Agatha Christie. From the research finding, there are 132 data of derivative adjective in Agatha Christie's The Murder of Roger Ackroyd into Pembunuhan atas Roger Ackroyd translated by Maria Regina which are found, and all of them are including to the literal translation type. From those 132 data, there are 96 data or 72,73% are including to the accurate derivative adjective translation and 36 data or 27,27% are including to the inaccurate one.